WASTE MANAGEMENT DEVELOPMENT STRATEGY BY BANK SAMPAH DALANG COLLECTION PEKANBARU CITY - Harapan Tua R.F.S; Nur Laila Meilani; Anita Anita (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The problem in this research is that garbage is not picked up every day causing a lot of piles of garbage in the city of Pekanbaru which has an impact on creating an unsanitary environment, this is of course inseparable from the lack of public awareness regarding waste management, especially the city of Pekanbaru. The purpose of this study was to analyze the development strategy in waste management by the Dalang Collection waste bank in Pekanbaru and to analyze the factors that influence the development of waste management in the Dalang Collection waste bank. This research uses descriptive qualitative method with SWOT analysis. The results of this study indicate that the strategy in developing the dalang collection waste bank can be said to be optimal, namely in the form of planning, training, outreach and visits that have been realized through increased activities for the community. From the results of the study, the proposed strategy that can be used in developing the management of the dalang collection waste bank is to improve the internal quality of the organization by balancing external organizational factors and the factors that influence the strategy for developing the waste management of the dalang collection waste bank, namely support from the government, customer loyalty and facilities adequate infrastructure.